PENGEMBANGAN KEPRIBADIAN KONSELOR YANG ISLAMI DI ERA MILENIAL - Ika Purnama Sari (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2021)
Guidance and counseling services are services intended for students, both for students who have problems and students who do not have problems. Guidance and counseling services in schools as an effort from guidance and counseling teachers to assist students in optimizing the potential and independence of each student to solve the problems they experience, both problems in the personal, social, academic and academic fieldscareer field.Guidance and counseling teachers/counselors are fully responsible for providing guidance and counseling services to students by observing the long-term impact of the services provided to students. In order to realize optimal guidance and counseling services, guidance and counseling services must be provided by professional guidance and counseling teachers